"Eles torturavam as crianças na frente das mulheres": mulheres, trauma e maternidade na resistência à ditadura militar brasileira - Corrêa, Ana Paula Alves (2018)
The present research, in the field of Pecheux’s French Discourse Analysis, has the objective of proposing a reflection on the place that the subject woman occupies in the conditions of prison production and feminine torture, during the Brazilian military dictatorship (1964 -1985), in which the feminine body is treated different from the masculine in what he/she refers to the torture forms. We leaned over on the problem of the maternity that permeates the discursive processes in operation in the production conditions referred, making possible a possible place of visibility of the confrontation among the position subject-woman, the subject-militant position and the position subject-mother, of the discursive point of view. As premise for our reflection, we selected, in the work it Luta, Substantivo Feminino: Mulheres torturadas, desaparecidas e mortas na resistência à ditadura, organized by Tatiana Merlino and Igor Ojeda (2010), six testimonies of women that were arrested and tortured during the Brazilian military dictatorship, of which we made cuttings of the statements in that the militants tell threats to their children and the senses that such action wakes up in them. Leaning in those cuttings, we were devoted to understand as the desestabilização of the senses is produced concerning the one that is be woman, that is to be militant and of the one that is be mother. With base in the developed study, we understood that, for the ideological interpellation, the woman / militant / mother taking one of those positions, it doesn't turn off his/her previous position, therefore it is not possible saying of a mother's place, without carrying the woman's saying and the militant's saying. With that, we affirmed that the silence was the alternative found by the women, in the production conditions in that you/they were, and that, for the absence of the saying, if it produced a resistance form to the torture. The silence, here expert as incompletude place, division and production of senses always other, he/she attests for the intimate relationship among the subject, the language and the world. In the analyzed cuttings, we highlighted as the testimonies produced by those militants are organized around the maternity, that is, of the "being mother" as a historical and ideological construction, in the which different discursive formations are crossed that they sustain his/her saying for the operation of the memory, of the politician and of the symbolic. The child is understood, for the torturer, as an extension of the mother, and for the work of the ideology you/he/she is always already-subject, meant and meaning in the effective social practices. In the theoretical perspective in the which we based ourselves, there is no sense and there is no full subject, as well as no there is a full identification. Like this, we concluded that the production of senses on being "mother", in the attempt of destabilizing the resistance feminine front the dictatorship, doesn't turn off position-subject woman and militant, because she resists in the / for the silence, not stopping meaning.